The probiotic effects of dietary inactive yeast Saccharomyces cerevisiae var. ellipsoideus on growth factors, survival, body composition and intestinal microbiota of Beluga juvenile (Huso huso) - Hoseinifar, S.H.; Mirvaghefi, A.R.; Mojazi Amiri, B.; Khoshbavar Rostami, H.A.; Poor Amini, M.; Darvish Bastami, K. (2011)
The probiotic effects of inactive yeast, Saccharomyces cerevisiae var. ellipsoideus was studied on growth performance, survival and intestinal microbiota of beluga juveniles (Huso huso). The study was done in complete randomize design that included feeding of beluga juveniles with diets supplemented with 0 (control), 1, 2 and 5% yeast (4 treatments with 3 replicates). Beluga juveniles (11.40±0.56g) were randomly allocated in 12 oval tanks at a density of 35 fish per tank and triplicate group were fed with experimental diets. At the end of the trial, growth factors (final weight, weight gain, SGR, CF) as well as feed conversion ratio (FCR), body composition (protein, lipid, ash, moisture) and intestinal microbiota (total viable bacteria and Lactobacillus spp. levels) were determined. Our results confirmed that juveniles fed on diet supplemented with 5% S. cerevisiae var. ellipsoideus had significantly higher final weight, weight gain, specific growth rate (SGR) and lower food conversion ratio compared to control and 1% treatment (P<0.05). However, there were no significant differences between SGR of 5 and 2% yeast treatments (P>0.05). The study of body composition showed no significant difference between treatments (P>0.05). Total viable bacteria and Lactobacillus spp. count were significantly higher in 5% treatment compared to control (P<0.05). However, there was no significant difference between Lactobacillus spp. levels in 5 and 2% treatments (P>0.05).